2004
DOI: 10.1038/modpathol.3800014
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of core needle biopsy diagnosis in assessing papillary breast lesions: histologic predictors of malignancy

Abstract: The purpose of this study was to determine the accuracy of core needle biopsy (CNB) diagnosis of papillary breast lesions and to identify histologic features that can predict malignancy. We retrospectively reviewed 2876 CNB performed at MD Anderson Cancer Center (01/95-08/02) and identified 50 papillary lesions: 30 papillomas, eight atypical papillomas and 12 papillary carcinomas. Histopathological parameters were evaluated and radiographic findings were reviewed. When available, the CNB was compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
73
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(76 citation statements)
references
References 12 publications
1
73
2
Order By: Relevance
“…The location of the papillary lesion is another widely studied risk factor. Some studies reported a tendency for the papillary lesion to be malignant if it was located at the periphery of the breast (19,20), whereas no such association was found in many other studies, including the present study (3,6,8).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The location of the papillary lesion is another widely studied risk factor. Some studies reported a tendency for the papillary lesion to be malignant if it was located at the periphery of the breast (19,20), whereas no such association was found in many other studies, including the present study (3,6,8).…”
Section: Discussioncontrasting
confidence: 51%
“…Reported upgrading rates from benign papillary lesions diagnosed by CNB to malignant papillary lesions diagnosed on subsequent surgical excision range from 0% to 29% (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Some investigators have suggested that benign papillary lesions without atypia diagnosed by CNB, in combination with concordant imaging findings, can be safely followed without further surgery (2-7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the radiology-pathology correlation data are either missing or incomplete in many studies. 4 Studies that have included radiology-pathology correlation for core biopsy cases with papillomas 22,23 and lobular neoplasia [24][25][26] tend to report lower upgrade rates and may argue against mandatory excision for these diagnoses on core biopsy. Similarly, our overall upgrade rate of 7% for cases with careful correlation is lower than the majority of published studies with 30 or more excisions (Table 4) and closer to the 9.5% reported by Bianchi et al 27 in a series of 589 cases from multiple hospitals in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is accepted practice that intraductal papillomas with associated atypia or malignancy diagnosed on core needle biopsy must be excised, [1][2][3][4][5] the treatment of pure intraductal papillomas, that is, without atypia or malignancy diagnosed on core needle biopsy was and remains controversial. 1,6 Earlier series attempting to resolve these issues indicated a small but definite risk for atypia (15%-37.5%) or malignancy (15%-17%).…”
mentioning
confidence: 99%